Pengaruh Pengetahuan, Sosialisasi, dan Reformasi Perpajakan terhadap Kepatuhan Wajib Pajak Generasi Z: Peran Kesadaran Wajib Pajak sebagai Variabel Moderasi - Sri Winarni; Muhammad Rifaldi; Tiolina Evi Nausta Pardede (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the effects of tax knowledge, tax socialization, and tax reform on the tax compliance of Generation Z individual taxpayers in the Jabodetabek region, with taxpayer awareness serving as a moderating variable. The study employs a quantitative approach with a sample of 175 individual taxpayers selected through stratified random sampling, and the data are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that tax knowledge, tax socialization, and tax reform have a positive and significant effect on taxpayer compliance, while taxpayer awareness is not proven to significantly moderate the relationship between the independent variables and taxpayer compliance. These findings suggest that Generation Z’s tax compliance is more strongly influenced by cognitive and systemic factors, such as tax understanding and system modernization, rather than by internal awareness as a reinforcing factor. Therefore, this study emphasizes the importance of digitally based tax education strategies and adaptive tax reform initiatives that align with the characteristics of Generation Z.